Acute inactivation of the Aspergillus nidulans Golgi membrane fusion machinery: correlation of apical extension arrest and tip swelling with cisternal disorganization. Issue 2 (14th June 2013) - Pinar, Mario; Pantazopoulou, Areti; Arst, Herbert N.; Peñalva, Miguel A.
Summary: The mechanisms governing traffic across the Golgi are incompletely understood. We studied, by live‐cell microscopy, the consequences of disorganizing the Aspergillus nidulans  Golgi, using an extended set of fluorescent protein markers to resolve early from late cisternae. The early Golgi syntaxin SedV Sed 5 and the RabO Rab 1 regulatory GTPase play essential roles in secretion, cooperating in the ER–Golgi interface. Following a temperature shift‐up 'on‐the‐stage', hyphae carrying engineered sedV R258G and rabO A136D   ts mutations arrest polarized growth. This arrest correlates with overall Golgi disorganization and characteristic hyphal tip swelling. Using v‐SNARE SynA as reporter, we show that the sedV R258G phenotypes correlate with arrested secretion. Both the morphogenetic defect and the secretory deficit are reversible. Thus downregulation of secretion, like that of endocytosis, has morphogenetic consequences, implying that mechanisms tuning the secretory pathway might be involved in developmental processes. According to the cisternal maturation model, acute impairment of traffic in the ER–Golgi interface should lead to disorganization of both the early and the late Golgi cisternae. Thus, the relatively rapid late Golgi disorganization observed upon shifting ER–Golgi interface mutants to the restrictive temperature seems incompatible with an A. nidulans  Golgi network organized on the basis of stable early and late compartments, supporting instead cisternal maturation.